Prevalence of Cerebral Palsy among 8‐Year‐Old Children in 2010 and Preliminary Evidence of Trends in Its Relationship to Low Birthweight. Issue 5 (23rd May 2016) - Durkin, Maureen S.; Benedict, Ruth E.; Christensen, Deborah; Dubois, Lindsay A.; Fitzgerald, Robert T.; Kirby, Russell S.; Maenner, Matthew J.; Van Naarden Braun, Kim; Wingate, Martha S.; Yeargin‐Allsopp, Marshalyn
Abstract: Background: The public health objective for cerebral palsy (CP) in the United States is to reduce the percentage of children with CP who were born low birthweight (LBW, <2500 g) by 10% between 2006 and 2020. This study reports the prevalence of CP in a constant surveillance area for the years 2006, 2008, and 2010 and describes initial progress towards the CP public health objective. Methods: Data on children with CP at age 8 years were ascertained by the Autism and Developmental Disabilities Monitoring (ADDM) Network, a population‐based surveillance system that monitored CP in four areas of the United States. Results: CP prevalence in 2010 was 2.9 per 1000 [95% confidence interval (CI) 2.6, 3.2], down from 3.5 (95% CI 3.2, 3.9) in the same surveillance area in 2006. Among CP cases with no documented postneonatal aetiology, 49.1% (95% CI 42.9, 55.2) were born LBW in 2010 compared with 54.3% (95% CI 48.4, 60.1) in 2006. In 2010, 28.1% (95% CI 22.9, 30.4) were born very low birthweight (VLBW, <1500 g) compared with 35.4% (95% CI 30.0, 41.2) in 2006. The relative risks for associations between CP and both LBW and VLBW also declined, though not significantly, during the study period. Conclusions: Declines in the associations between CP and LBW categories may have contributed to declines during the study period in both the prevalence of CP and the percentage of children with CP who were born LBW or VLBW. Ongoing monitoring of these trends is warranted.